HafAn: a R-language script aiding interpretation of the Hf isotopic data - Janousek,V. (Journal of Geosciences, 2024)
HafAn is a new R-language script for recalculation, statistical treatment and graphical presentation of the Hf isotopic data from whole-rock samples or, more commonly, obtained in situ (e.g. by LA MC ICP-MS) from igneous, metamorphic and detrital zircon. Besides the recalculation of the present-day Hf isotopic ratios to initial ones, epsilon values and various variants of model ages, it allows presentation of such univariate data in the form of histograms, boxplots, stripplots and violin plots. Arguably the most telling and sophisticated way of displaying the Hf isotopic data are the Hf isotopic growth (age-176Hf/177Hf or epsilon Hf) diagrams. The HafAn has been designed as a plugin module for the Geochemical Data Toolkit (aka GCDkit), a well-established system for interpretation of the whole-rock geochemical data. This approach potentially allows interpretation (and plotting) of the Hf isotopic data jointly with the rest of the chemical and/or isotopic signature, as well as merging or overplotting several datasets on a single diagram. Moreover, R/GCDkit contains a plethora of additional statistical tools that can be newly applied to the Hf isotopic data as well. Our HafAn also profits from a wide palette of the file formats available for reading data input, as well as exporting results and graphical output. The HafAn plugin, together with all the GCDkit-family tools, can be downloaded from https://gcdkit.org
Keywords: Hf isotopes; zircon; software; R language; GCDkit; FOSS